Fibroblasts‐dependent invasion of podoplanin‐positive cancer stem cells in squamous cell carcinoma. Issue 10 (9th February 2020) - Miyashita, Tomoyuki; Neri, Shinya; Hashimoto, Hiroko; Akutsu, Asami; Sugano, Masato; Fujii, Satoshi; Ochiai, Atsushi; Ishii, Genichiro
Abstract: To clear whether podoplanin‐positive cancer stem cells in squamous cell carcinoma have higher invasion activity during a fibroblasts‐dependent invasion. A collagen gel invasion assay was performed using fluorescent ubiquitination‐based cell cycle indicator‐labeled A431 cells. The total number and number of invading cells in S/G2/M phase were counted using time‐lapse imaging cocultured with fibroblasts. There was no significant difference between the number of invading podoplanin‐positive and negative A431 cells when fibroblasts did not exist. On the contrary, the number of invading podoplanin‐positive cells was significantly higher when fibroblasts existed. The frequency of cells in S/G2/M phase among invasion was no difference. Knockdown of podoplanin decreased the number of invaded A431 cells significantly when fibroblasts existed. Podoplanin‐positive A431 cells display higher invasion activity when fibroblasts exist, suggesting that some biological functions of cancer stem cells might become evident only within the fibrous tumor microenvironment. Abstract : Scheme of the fibroblast‐dependent invasion of podoplanin (+) cancer stem cells/tumor‐initiating cells.